2019
DOI: 10.1002/ccd.28112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of myocardial microcirculatory perfusion after catheter‐administered intracoronary thrombolysis with anisodamine versus standard thrombus aspiration in patients with ST‐elevation myocardial infarction

Abstract: Objective To evaluate efficacy, safety and feasibility of targeted intracoronary injection using pro‐urokinase combined with anisodamine (TCA) versus thrombus aspiration (TA) in ST‐elevation myocardial infarction (STEMI) patients with high thrombus loads. Background The best method of avoiding thrombus detachment and stroke in PCI patients with high thrombus loads has not yet been established. Methods STEMI patients receiving coronary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…Although routine thrombus aspiration is not recommended during primary PCI, thrombus aspiration may be considered in cases where a large residual thrombus burden is encountered after opening the vessel with the wire or balloon ( 9 , 12 ). About 80% of the patients in our trial had high-grade thrombus (TIMI 4–5) in the culprit artery, and around half the patients underwent manual thrombus aspiration, which is a higher proportion than that reported in other studies of intracoronary tirofiban or fibrinolytic therapy ( 21 23 , 38 , 39 ). Importantly, thrombus aspiration was not associated with stroke or transient ischemic attack in our trial.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Although routine thrombus aspiration is not recommended during primary PCI, thrombus aspiration may be considered in cases where a large residual thrombus burden is encountered after opening the vessel with the wire or balloon ( 9 , 12 ). About 80% of the patients in our trial had high-grade thrombus (TIMI 4–5) in the culprit artery, and around half the patients underwent manual thrombus aspiration, which is a higher proportion than that reported in other studies of intracoronary tirofiban or fibrinolytic therapy ( 21 23 , 38 , 39 ). Importantly, thrombus aspiration was not associated with stroke or transient ischemic attack in our trial.…”
Section: Discussioncontrasting
confidence: 51%
“…Another randomized clinical trial utilized low-dose alteplase (10-20 mg) for intracoronary administration (21). The dose of pro-UK used in the present study was selected based on the results of previous investigations, which suggested that local administration of 10-20 mg pro-UK could promote thrombus dissolution and improve myocardial perfusion without increasing the incidence of major bleeding events (38,39). In order to reduce the risk of bleeding complications in this study, patients with risk factors for bleeding were excluded, and the PCI procedures were performed via the radial artery.…”
Section: Data Are Presented As Mean ± Standard Deviation Median (Interquartile Range) or N (%) Ctfc Corrected Thrombolysis In Myocardial mentioning
confidence: 99%
“…Eleven corresponding authors were contacted for missing data, two of them responded, and only one provided clarification. Twelve trials [ 77 – 88 ] were included after eliminating 64 studies for various reasons (S3 Table in S1 File ). In addition, results from a one-year follow-up [ 89 ] of one included study [ 83 ] were considered in the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The 12 trials enrolling 1,466 patients were conducted in different countries between 2009 and 2018. Six studies recruiting 647 patients (44.1%) were from China [ 77 , 79 , 80 , 85 , 86 , 88 ]. Recruitment periods ranged from 0.5 to 5.4 years and sample size from 39 to 452 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of this study was calculated based on previous studies [13,14]. Assuming the IMR in the intracoronary prourokinase group was 30 U (SD = 10) and 40 U (SD = 13) in the control group, with a power of 90%, a two-sided 5% level of significance (α) and a sample size ratio of 1:1, required a sample size of 20 participants in the intracoronary prourokinase group and 20 in control group.…”
Section: Discussionmentioning
confidence: 99%